Clinico-Histopathological Analysis and Bacillary Index in a Study of Skin Biopsies of Leprosy Patients (GAIMS Journal of Medical Sciences, 2023)
Introduction: Leprosy is one of the leading causes of physical disabilities contributing to intense social stigmata resulting in human discrimination. This chronic infectious disease caused by Mycobacterium leprae principally affects skin. Histopathology study and bacillary index is important in understanding the disease progression, diagnosis, varied manifestation and complications.Aim: To study the histopathological features of leprosy in skin biopsies, categorize them into various types and correlate Bacillary Index with clinical presentation whenever possible.Materials & Methods: Skin biopsy specimen was obtained from clinically diagnosed 100 cases of Leprosy  patients attending Skin OPD. Specimen stained with Hematoxylin & Eosin and 5%AFB.Results: The age of the patients was ranged from 4 to 80 years. The male to female ratio  was 3:1. Borderline Tuberculoid was the most common presentation. Clinco- histopathological agreement was seen in  76 (76%) cases.Conclusions: The clinical and histopathological features along with bacteriological index are useful than any single parameter in arriving definitive diagnosis and classification of the leprosy.